2019
DOI: 10.1111/epi.16375
|View full text |Cite
|
Sign up to set email alerts
|

Tau deposition in young adults with drug‐resistant focal epilepsy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract Objective: To evaluate the presence of tau deposition and pathologic features of chronic traumatic encephalopathy (CTE) in young adult patients treated with focal cortical resections for drug-resistant epilepsy. Methods: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…This association was based on evidence that epileptic seizures and cognitive deficits are frequently reported in patients with Alzheimer's Disease (AD), the most common form of tauopathies (Amatniek et al, 2006;Palop and Mucke, 2009). Analysis of surgically resected epileptic brains revealed similar pathologies to those observed in AD including abnormally phosphorylated tau and increased amyloid precursor protein (APP) (Thom et al, 2011;Tai et al, 2016;Smith et al, 2019;Gourmaud et al, 2020). In addition to tau pathology, increased Fyn expression was evident in AD brains (Shirazi and Wood, 1993;Ho et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This association was based on evidence that epileptic seizures and cognitive deficits are frequently reported in patients with Alzheimer's Disease (AD), the most common form of tauopathies (Amatniek et al, 2006;Palop and Mucke, 2009). Analysis of surgically resected epileptic brains revealed similar pathologies to those observed in AD including abnormally phosphorylated tau and increased amyloid precursor protein (APP) (Thom et al, 2011;Tai et al, 2016;Smith et al, 2019;Gourmaud et al, 2020). In addition to tau pathology, increased Fyn expression was evident in AD brains (Shirazi and Wood, 1993;Ho et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperphosphorylation of tau hinders its degradation, thus leading to the aggregation of tau and forming of neurotoxic paired helices ( Sadqi et al, 2002 ). Abnormal accumulation of hyperphosphorylated tau in the hippocampus or appearance of neuropil threads and NFTs in the resected epileptogenic temporal lobe has been reported in a majority of epilepsy patients ( Tai et al, 2016 ; Smith et al, 2019 ). Consistently, we found that repeated induction of seizures prominently elevated phosphorylated and total tau levels in the cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperphosphorylation and intracellular accumulation of tau protein dysregulate microtubule assembly and aggravate the formation of neurofibrillary tangles, thus remodeling neuronal synapses and exacerbating cognitive decline in a collection of diseases named tauopathies, including Alzheimer disease (AD; Wang et al, 2014 ; Wang and Mandelkow, 2016 ; Yang and Wang, 2018 ). Recent studies also revealed prominent accumulation of hyperphosphorylated tau in the brain of temporal lobe epilepsy patients ( Tai et al, 2016 ; Smith et al, 2019 ). Given that epilepsy and early stage AD share many neurological characters and psychiatric symptoms ( Kanner, 2009 ; Cheng et al, 2015 ; Zarea et al, 2016 ), we wonder whether tau pathology also contributes to the cognitive deficits in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patterns of hippocampal atrophy and connectivity observed in AD mimic those seen in mesial temporal epilepsy (61,72,138–140). Hyperphosphorylated tau has been found even in young patients with refractive focal epilepsy and correlated with cognitive decline, suggesting that seizures may in turn contribute to progressive AD pathology (141,142).…”
Section: Circuit Dysfunction In Ad: Evidence From Human Studiesmentioning
confidence: 99%